Foot Exams in a Student-Run Clinic - Jeremy Steinman; Marlena Wosiski-Kuhn; Devin Haddad; John Ramos; Kathryn E Callahan (Journal of Student-Run Clinics, 2017)
Background: Chronic diabetes management is challenging in any clinic. A quality improvement study addressed the barriers affecting diabetic foot examination rates in a student-run clinic. Methods: Between February 1, 2013 and December 31, 2015, providers received education about exam components and reminders to perform the exam. Two reminder phases were implemented: 1) inked stamps in the chart and 2) Diabetes Care Forms (a half sheet explaining the exam and streamlining documentation). All encounters for patients with diabetes (451) were retrospectively selected from an internal database for analysis of the presence or absence of chart reminders and diabetic foot examinations. Microsoft Excel was used for basic statistical analysis and chart propagation; SAS was used for chi-square testing. Results: Pre-intervention encounters had an exam rate of 33% (43/107). During the stamp-based intervention between February 1, 2013 and January 31, 2014, the overall exam rate was 78% (86/110, p<0.0001 from baseline) and 90% with the presence of a stamp (81/90, p<0.0005 from pre-intervention). During the Diabetes Care Form (DCF) intervention between February 1, 2014 and December 31, 2015, the overall exam rate was 83% (158/191, p<0.0001 from baseline, p>0.10 from stamp intervention) and 97% for the charts with a DCF (143/148, p<0.0001 from baseline, p<0.05 from stamp intervention).Conclusions: Academic detailing and visual reminders are effective techniques to improve the rate of diabetic foot examinations. A half sheet of paper serving as documentation and as a reminder increased the rate of foot exams in a student-run free clinic with paper charts and rotating clinical staff.